Sistem Informasi Geografis Pemetaan Pondok Pesantren Di Kabupaten Kendal Tahun 2023-2024 - Hanum Nahla Zahrani; Bambang Agus Herlambang; Ahmad Khoirul Anam (JOURNAL SAINS STUDENT RESEARCH, 2026)
Islamic boarding schools (pesantren) are one of the rapidly growing Islamic educational institutions in Kendal Regency. This study aims to analyze how Islamic boarding schools are distributed in Kendal Regency from 2023 to 2024 using a Geographic Information System (GIS). This study uses a comparative descriptive method with data consisting of spatial data in the form of sub-district administrative maps and non-spatial data covering the number of Islamic boarding schools, students, and teachers. The non-spatial data comes from the Central Statistics Agency (BPS) of Kendal Regency. To process the data, the QGIS application is used. Spatial and non-spatial data are combined in the attribute merging process, then converted into a thematic map. The results show a decrease in the number of Islamic boarding schools from 147 in 2023 to 118 in 2024, as well as an uneven decrease in the number of students and teachers in each sub-district. The resulting thematic map is able to clearly and informatively show differences in the distribution of Islamic boarding schools.